Use of Alizarin Red S as an Ion-Pair Reagent for the Spectrophotometric Assay of Fexofenadine in Pharmaceuticals and in Spiked Human Urine. (19th December 2012) - Raghu, Madihalli S.; Basavaiah, Kanakapura; Prashanth, Kudige N.; Vinay, Kankapura B.
Abstract : The present study describes two simple, rapid, selective, and cost-effective spectrophotometric methods for the determination of an antiallergic drug, fexofenadine hydrochloride (FFH), in bulk drug, tablets, and in spiked human urine. The first method (method A) is based on the formation of yellow-colored ion-pair complex between FFH and alizarin red S (AZS) in acid medium which was extracted into dichloromethane, and the absorbance was measured at 440 nm. The second method (method B) is based on the breaking of the yellow FFH–AZS ion-pair complex in alkaline medium followed by the measurement of the violet-colored free dye at 590 nm. Under the optimized conditions, Beer's law is obeyed over the concentration ranges of 0.4–12.0 and 0.2–3.5  μ g m L - 1 FFH for method A and method B, respectively, and the corresponding molar absorptivity values are 3.80 × 10 4 and 1.61 × 10 5  L mo l - 1   c m - 1 . The Sandell's sensitivity, detection, and quantification limits are also reported. The proposed methods were successfully applied to the determination of FFH in pure drug and commercial tablets. The accuracy and reliability of the proposed methods were further established by recovery studies via standard addition technique.